2022
DOI: 10.3389/fsurg.2022.1049685
|View full text |Cite
|
Sign up to set email alerts
|

High fidelity simulation of the endoscopic transsphenoidal approach: Validation of the UpSurgeOn TNS Box

Abstract: ObjectiveEndoscopic endonasal transsphenoidal surgery is an established technique for the resection of sellar and suprasellar lesions. The approach is technically challenging and has a steep learning curve. Simulation is a growing training tool, allowing the acquisition of technical skills pre-clinically and potentially resulting in a shorter clinical learning curve. We sought validation of the UpSurgeOn Transsphenoidal (TNS) Box for the endoscopic endonasal transsphenoidal approach to the pituitary fossa.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…A randomised cross-over study was conducted using a validated phantom model for the eTSA (UpSurgeOn Transsphenoidal (TNS) Box). 8 The TNS Box was prepared by creating a surgical corridor such that the tumour was accessible. Participants were tasked with performing a tumour resection after a short standardised introduction to the robot and standard instrument.…”
Section: Methodsmentioning
confidence: 99%
“…A randomised cross-over study was conducted using a validated phantom model for the eTSA (UpSurgeOn Transsphenoidal (TNS) Box). 8 The TNS Box was prepared by creating a surgical corridor such that the tumour was accessible. Participants were tasked with performing a tumour resection after a short standardised introduction to the robot and standard instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen studies of simulation with synthetic models were identified. 11,15,[27][28][29][30][31][32][33][34][35][36][37][38] 2. 11,15 In Maza et al, both neurosurgery and otolaryngology residents and attendings were included and the pre/post-TTH were 105 and 40 sec while the pre/post-EBL were 690 and 272 mL.…”
Section: Synthetic Modelsmentioning
confidence: 99%
“…the face and content validity of synthetic models in acquisition of anatomical knowledge and surgical expertise in EEN. 27,[29][30][31]35,36 Oyama et al described one of the most complete synthetic simulation models, in which the anterior, middle, and posterior fossa could be accessed through both sagittal and coronal plane approaches. 31 [29][30][31][32]35,36,38 whereas Wen et al…”
Section: Synthetic Modelsmentioning
confidence: 99%
See 2 more Smart Citations